Post-Symbolic Images in Platform Capitalism: An “Impolitical” Aesthetic Space (Materiali di Estetica. Terza serie, 2022)
Platform capitalism brings several processes to completion that were already apparent during post-industrial capitalism. One of these involves images and their gradual loss of a symbolic dimension. The mechanisms that platforms employ to direct the production of media content reduce images to objects of immediate use and consumption. Consequently, images fail to synthetise the multiplicity of the social reality: instead of inscribing it within a horizon of meaning, they simply reflect it. This article reconstructs the “de-symbolising” process of images during the various phases of capitalism and explains why a post-symbolic aesthetics should also be viewed as “impolitical”. If the political is indeed symbolic, since the giving of meaning and direction to society (a political task par excellence) also takes place through the construction of symbolic systems, the post-symbolic aesthetic is instead imposed by platforms for purely economic reasons.
Keywords: Symbol; Platform Capitalism; Post-industrial Capitalism; Aesthetics